2023
DOI: 10.1021/acsami.2c17901
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Composite Electrodes of Carbon Nanotube Fabrics and Inorganic Matrices via Rapid Joule Heating

Abstract: Composites of nanocarbon network structures are interesting materials, combining mechanical properties and electrical conductivity superior to those of granular systems. Hence, they are envisaged to have applications as electrodes for energy storage and transfer. Here, we show a new processing route using Joule heating for a nanostructured network composite of carbon nanotube (CNT) fabrics and an inorganic phase (namely, MoS 2 ), and then study the resulting structure and properties. To this end, first, a unid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…Joule heating also provides a direct path for inside‐out crystallization of the conformal MoS 2 layer, enabling excellent interfacial interaction between the MoS 2 and the underlying carbon‐based material (e.g., 2D graphene). [ 71 ] Due to extremely quick heating, simple processing, and ability to integrate with textiles [ 70 ] and other components, [ 72 ] in our study we investigated various configurations of graphene and MoS 2 heterostructure layers to create conductive heating textiles where glass fiber fabric was coated with these 2D materials (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…Joule heating also provides a direct path for inside‐out crystallization of the conformal MoS 2 layer, enabling excellent interfacial interaction between the MoS 2 and the underlying carbon‐based material (e.g., 2D graphene). [ 71 ] Due to extremely quick heating, simple processing, and ability to integrate with textiles [ 70 ] and other components, [ 72 ] in our study we investigated various configurations of graphene and MoS 2 heterostructure layers to create conductive heating textiles where glass fiber fabric was coated with these 2D materials (Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported that introducing an electric field during heating can effectively enhance the material's conductivity. 15,16 In this study, Joule heating was employed to achieve rapid temperature elevation. Among various Joule heating devices, 17,18 to allow current to pass through the carbon material, we adopted the flash Joule heating (FJH) method reported by Tour's team, 19 which boasts rapid reaction time and high reaction temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the conductivity of carbon materials from direct pyrolysis is unsatisfactory, failing to meet the demands of high-rate charging and discharging. Some studies have reported that introducing an electric field during heating can effectively enhance the material’s conductivity. , …”
Section: Introductionmentioning
confidence: 99%
“…The use of Joule heating methodology of flash heating with has a unique kind of technique which produce nanoparticles mixing in well dispersed way. Upama et al [29] investigated joule heating for electrodes of nanotube and inorganic matrices with composite electrodes. Celik et al [30] discussed joule heating numerically and experimental investigations are also done for carbon fibre powder epoxy.…”
Section: Introductionmentioning
confidence: 99%